KNOWLEDGE PRODUCTION ON CONTINUOUS PROFESSIONAL LEARNING OF PHYSICAL EDUCATION TEACHERS: AN ANALYSIS BETWEEN BRAZILIAN AND INTERNATIONAL STUDIES - Alexander Barreiros Cardoso Bomfim; Sheila Aparecida Pereira dos Santos Silva; Maria Luiza de Jesus Miranda (Journal of Physical Education)
ABSTRACT This article analyzes knowledge production on continued training of physical education teachers in the Education Resources Information Center (ERIC) database and a collection of 14 Brazilian journals. The goal is to provide an overview on scientific production and discuss the search options adopted by researchers, identifying developments and trends. There has been a transition in the 15-year period analyzed (2000-2014) and a prevalence of studies emphasizing the participants history. There was a predominance of phenomenological-hermeneutical studies regarding the epistemology and of qualitative studies regarding the research methods. Our data suggest that there is room to investigate the continued professional training, perceiving teachers as researchers of their practice and transforming agents of their reality.